Cancer research and the mainstream of biology - Maimets, Toivo (Frontiers in Cell and Developmental Biology, 2025)
John Cairns, a British molecular biologist, has pointed out that biology and cancer research have always developed together, and cancer theories have followed “whatever branch of biology happens at the time to be fashionable and exciting”. Indeed, following the long historical development of biological thought confirms this observation. However, tumour theories have never been merely a “fellow runner” to more modern biology theories. Cancer is an exceptionally large medical and economic problem, and the practical results of cancer research are carefully followed and critically analysed by the community. If the expected results do not arrive and the scientific data do not fit into the old theory, then the theory must be corrected. In other words, tumour theories not only derive from the prevailing biological worldview, but they also influence and, if necessary, actively change it. That is exactly what we are witnessing today–the ruling reductionist Somatic Mutations Theory (SMT) does not explain many new experimental findings and extensive research over the last 50 years has not brought major breakthroughs in cancer treatment. This century brings back the attention to developmental biology (embryology) in connection with the epigenetic revolution in biology, and the causes of tumours are searched for in the disorders of differentiation of cells/tissues and communication between them in the organism.